AWARENESS OF HEALTH RISKS OF DIRTY COOKING FUELS AND DEMAND FOR COOKING FUELS IN JOS METROPOLITAN CITY, NIGERIA - Vonke Juliana Dickson; Yerima Ishaya Jabil; Philip Enyinnaya Dickson; Faith Onechojo Etuh; Onyinnyechi Josephine Onuoha (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
This paper investigated the influence of the awareness of health risks of ‘dirty’ cooking fuels on the demand for cooking fuels among households in Jos metropolitan city. The study adopted qualitative research design. Key Informant Interviews (KIIs) were conducted with 16 households’ decision makers. Results of the study showed that households in Jos metropolitan city use a combination of cooking fuels: liquefied petroleum gas, which is the primary cooking fuel, charcoal and firewood, which are secondary. Convenience and cost are the main determinants of the choice of cooking fuel (and also inform the cooking fuel stacking), quantity of food, cooking duration and cooking place are other determinants. There is evidence of the awareness of the risks associated with ‘dirty’ cooking fuels. However, the awareness is not strong enough to deter the households in Jos metropolis from using ‘dirty’ cooking fuels, because they erroneously think that they can avert the health risks. Studies that considered ‘awareness of health risks of ‘dirty’ cooking fuels’ as determinant of the choice of cooking fuel are limited. This study is an addition to literature in the area.